Formulation And Evaluation Of Rifampicin And Gatifloxacin Niosomes On Logarithmic-Phase Cultures Of Mycobacterium Tuberculosis - N.PAVALA RANI; T.N.K.SURIYAPRAKASH; R.SENTHAMARAI (International Journal of Pharma and Bio Sciences, 2010)
Niosomes are vesicles mainly consisting of non-ionic surfactants that encloses and encompasses the drug molecules. Niosomes of rifampicin and gatifloxacin were prepared by lipid hydration technique using rotary flash evaporator. The prepared rifampicin and gatifloxacin niosomes showed a vesicle size in the range of 100-300nm, the entrapment efficiency were 73% and 70% respectively. The invitro release study showed that 98.98% and 97.74% of release of rifampicin and gatifloxacin niosomes respectively. The bactericidal activities of the niosomal formulation were studied by BACTEC radiometric method using the resistant strains (RF 8554) and sensitive strains (H37Rv) of Mycobacterium tuberculosis which showed greater inhibition and reduced growth index.